Identifying Determinants of Competitive Advantage for Ayam Geprek Business in Jakarta During the Pandemic Covid-19 - Michael Christian; Justinius Justinius (Journal of Business & Applied Management, 2021)
The Covid-19 pandemic is a challenge for the food industry in Indonesia. Food entrepreneurs must think hard to create the strategies needed to survive, even though many decide to close their businesses. Conducting an analysis of existing market conditions is something that must be done to support strategic decisions in creating and maintaining a competitive advantage. This study aims to identify the factors that influence the competitive advantage of Geprek Chicken in Jakarta. This study focuses on the research object, namely exogenous variables consisting of market orientation, product innovation, innovation process, and endogenous variables, namely competitive advantage. This research is a quantitative study using Partial Least Square - Structural Equation Modeling (PLS-SEM) modeling with SMART PLS 3.0 as an analysis tool. By using a non-probability sampling technique, the questionnaire was randomly distributed to 130 samples. However, only 77 questionnaires (59.23%) met the criteria for analysis. The results of this study explain that two hypotheses are accepted, and two hypotheses are rejected where market orientation affects innovation while innovation has no effect on competitive advantage. Based on the indirect effect, innovation as a mediator between market orientation towards competitive advantage does not act as mediator. Furthermore, these results indicate that Market Orientation, Process Innovation, and Product Innovation can explain the representation of the Competitive Advantage variable by 5.8%, meanwhile Market Orientation is able to explain its representation of the Process Innovation variable by 14.6 and the Market Orientation variable is able to explain its representation towards Product Innovation. by 0.9%. These results provide interesting results on the market orientation variable towards competitive advantage, especially contributing to priority findings during a pandemic such as Covid-19.